IMPLEMENTASI SISTEM INFORMASI MANAJEMEN SEKOLAH DALAM MENDUKUNG PELAYANAN PENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN MEGA BANGSA - Nurul Adli Gunawan; Ahmad Yudha Fahreza; Ali Mansur; Fuad Rabbani Ashidqi; Muhammad Fikri Juliansyah; Muhammad Raihan Anhar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the Education Management Information System (SIMDIK) is an important requirement for educational institutions to improve service quality, efficiency, and competitiveness in the era of globalization, in accordance with regulations such as Law No. 20 of 2003 concerning the National Education System and Regulation of the Minister of National Education No. 19 of 2007 concerning Education Management Standards. This article aims to analyze the implementation of the management information system at SMK Mega Bangsa in analyzing the factors that support and hinder it. This type of research is descriptive qualitative. The type of research used is field research, where this research was conducted in a specific environment, specifically at SMK Mega Bangsa. Data were collected through in-depth interviews with the principal, teachers, students, and administrative staff, as well as direct observation to understand the supporting and inhibiting factors in the implementation of SIMDIK. This study uses Edward III's Implementation Theory. Measurement indicators include communication, resources, layout and organizational structure. The implementation of the management information system is very important in educational institutions, especially at SMK Mega Bangsa, where data processing applications are used, especially Dapodik and IT technology to support the learning process by providing educational services by facilitating learning practices using technological infrastructure, such as computer-integrated learning facilities. Keywords: Implementation, Information Systems, Management Educational Services